Diversity and function of glial cell types in multiple sclerosis - Schirmer, Lucas; Schafer, Dorothy P.; Bartels, Theresa; Rowitch, David H.; Calabresi, Peter A. (Trends in immunology, 2021)
Glial subtype diversity is an emerging topic in neurobiology and immune-mediated neurological diseases such as multiple sclerosis (MS). We discuss recent conceptual and technological advances that allow a better understanding of the transcriptomic and functional heterogeneity of oligodendrocytes (OLs), astrocytes, and microglial cells under inflammatory-demyelinating conditions. Recent single cell transcriptomic studies suggest the occurrence of novel homeostatic and reactive glial subtypes and provide insight into the molecular events during disease progression. Multiplexed RNA in situ hybridization has enabled ‘mapping back’ dysregulated gene expression to glial subtypes within the MS lesion microenvironment. These findings suggest novel homeostatic and reactive glial-cell-type functions both in immune-related processes and neuroprotection relevant to understanding the pathology of MS.